Relationship of Milking Hygiene to the Presence of Staphylococcus aureus in Dairy Cow's Milk with Subclinical Mastitis - Sutiningsih, Dwi; Fitriyani, Fitriyani (Universitas Halu Oleo, 2022)
Subclinical mastitis is an infectious disease that mostly caused by Staphylococcus aureus. The presence of Staphylococcus aureus in the udder and the milk cows caused by several factors such as cleanliness of cows and sanitation. The purpose of this study is to analyze the relationship between milking hygiene factors to the presence of Staphylococcus aureus in milk of dairy cows with subclinical mastitis. This research is explanatory research surveys with cross sectional method. The experiment was conducted at the Village Sruni, Boyolali with the number of samples are 47 respondents. Data analysis with chi square. The results showed that there are relationship cleanliness of cows with Staphylococcus aureus bacterial counts (p = 0.039), and milking hygiene with the number of bacteria Staphylococcus aureus (p = 0.027), no relationship sanitation equipment and cage sanitation with the number of bacteria Staphylococcus aureus (p = 0.008) and (p = 0.23). The conclusion is there is association between sanitation and hygiene milking in the presence of Staphylococcus aureus in milk of dairy cows with subclinical mastitis sufferers in dairy cattle farming village Sruni, Musuk, Boyolali. It is recommended to breeders to pay attention to cleanliness of cows, milking hygiene and sanitation equipment before milking.Keywords: hygiene, dairy cow’s milk, milking, staphylococcus aureus, subclinical mastitis